Rhythm and its relation to the training of the deaf - Abano, Joceylyn Ibarreta 1941- (Quezon City College of Education, University of the Philippines Diliman, 1969)
This paper aimed to determine how rhythm is developed and how it affects the training of the deaf. Some rhythmic activities which can provide a wholesome activity for the deaf are moving to a drum beat, note values, and instruments. Rhythm for the deaf is an abstraction. It serves as a stimulus to physical, emotional and intellectual development. Through it one develops confidence and poise, thereby contributing to their social development and grace.
Vita.
Thesis (Master of Arts in Teaching - Special Education)--University of the Philippines, Diliman.
Keywords: Deaf children -- Education -- Philippines; Rhythm